Expression profiles of glucocorticoid-inducible proteins in human papilloma virus-related oropharyngeal squamous cell carcinoma - Mozaffari, Mahmood S.; Abdelsayed, Rafik; Emami, Sahar; Kavuri, Sravan (Frontiers in Oral Health, 2023)
Human papillomavirus virus-related oropharyngeal squamous cell carcinoma (HPV-OPSCC) comprises a significant portion of head and neck cancers. Several glucocorticoidinducible proteins play important roles in pathogenesis of some cancers but their status and roles in HPV-OPSCC remain elusive; these include the glucocorticoid-induced leucine zipper (GILZ), Annexin-A1 and serum glucocorticoid-regulated kinase-1 (SGK-1). Thus, we determined expression profiles of these proteins, using immunohistochemistry, in archived biopsy samples of patients diagnosed with HPV-OPSCC; samples of non-cancer oral lesions (e.g., hyperkeratosis) were used as controls. GILZ staining was primarily confined to nuclei of all tissues but, in HPV-OPSCC specimens, neoplastic cells exhibiting mitosis displayed prominent cytoplasmic GILZ expression. On the other hand, nuclear, cytoplasmic and membranous Annexin-A1 staining was observed in suprabasal cell layers of control specimens. A noted feature of the HPV-OPSCC specimens was few clusters of matured and differentiated non-basaloid cells that showed prominent nuclear and cytoplasmic Annexin-A1 staining while the remainder of the tumor mass was devoid of staining. Cytoplasmic and nuclear staining for SGK-1 was prominent for control than HPV-OPSCC specimens while staining for phosphorylated SGK-1 (pSGK-1; active) was prominent for cell membrane and cytoplasm of control specimens but HPV-OPSCC specimens showed mild and patchy nuclear and cytoplasmic staining. Semi-quantitative analysis of GILZ immunostaining indicated increased staining area but similar normalized staining for HPV-OPSCC compared to control specimens. By contrast, staining area and normalized staining were reduced for other proteins in HPV-OPSCC than control specimens. Our collective observations suggest differential cellular localization and expression of glucocorticoid-inducible proteins in HPV-OPSCC suggestive of different functional roles in pathogenesis of this condition.